INITIATION AND PROLIFERATION OF PAPAYA (Carica papaya L.) SOMATIC EMBRYOS FROM ZYGOTIC TISSUE - A. Ernawati; S. W. Adkins; R. A. Drew; I. D. Godwin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1999)
The stufy on the initiation and proliferation of somatic embryos from papaya (C. papaya L.) zygotic embryo explants was undertaken. Best results regarding initiation of embryogenic callus formation was obtained with 90 days after pollination (DAP) zygotic embryos. The medium were liquid and solid MS (0.5) medium containing glutamine (2.7 mM), 2,4-D (9 µM) and sucrose (170 mM) at 6 and 10 weeks after the start of the cultures. In this condition 90% explains produced embryogenic callus formation. The best medium for proliferation of somatic embryos was a liquid MS (0.5) medium containing glutamine (2.7 mM), sucrose (170 mM) in the presence of 2,4-D (9 µM). Using this medium, somatic embryos proliferated three times higher within two weeks.